2008
DOI: 10.1007/s10493-008-9226-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spirodiclofen on reproduction in a susceptible and resistant strain of Tetranychus urticae (Acari: Tetranychidae)

Abstract: In this study the reproductive capacity of a laboratory-selected spirodiclofen resistant strain was investigated after treatment with spirodiclofen. Firstly, females were exposed to different concentrations of spirodiclofen (200 and 1,000 mg/l) during 6, 12 or 24 h. In contrast to the susceptible parental strain, the fecundity and fertility of resistant mites was not affected by treatment with these concentrations after any time of exposure tested. Secondly, pre-treatment of the resistant females with the syne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 7 publications
5
36
1
2
Order By: Relevance
“…Moreover, the same symptomology of poisoning described previously for these two tetronic acid derivatives (Wachendorff et al 2002;Nauen et al 2005;Marcic 2007;van Pottelberge et al 2009;Marcic et al 2010a) was observed for spirotetramat, which points to the same mode of action of these three compounds on spider mites. Much stronger action of spirotetramat was registered on females treated at preovipositional period, compared to females treated at teleiochrysalis stage.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, the same symptomology of poisoning described previously for these two tetronic acid derivatives (Wachendorff et al 2002;Nauen et al 2005;Marcic 2007;van Pottelberge et al 2009;Marcic et al 2010a) was observed for spirotetramat, which points to the same mode of action of these three compounds on spider mites. Much stronger action of spirotetramat was registered on females treated at preovipositional period, compared to females treated at teleiochrysalis stage.…”
Section: Discussionsupporting
confidence: 82%
“…Spirodiclofen and spiromesifen are highly toxic to eggs and immatures of spider mites (Acari: Tetranychidae), whereas their activity against adult females is slower, with strong reduction of fecundity and fertility. In addition, spiromesifen acts similarly on juvenile stages and females of whiteflies (Wachendorff et al 2002;Nauen et al 2005;Bretschneider et al 2007;Marcic 2007;van Pottelberge et al 2009;Marcic et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Two hundred adult females were placed as the founding population and maintained on potted nonsprayed bean plants in a Panasonic climate chamber (MLR‐352H‐PE), at 28°C with a photoperiod of 16:8 hr light:dark. To assess etoxazole resistance over time, larval bioassays were performed as previously described by Van Pottelberge, Khajehali, Van Leeuwen, and Tirry (2009). Briefly, 50 adult females were allowed to lay eggs for 5 hr on the upper side of 9 cm 2 square‐cut bean leaf disks on wet cotton wool.…”
Section: Methodsmentioning
confidence: 99%
“…O espirodiclofeno atua no desenvolvimento dos ácaros inibindo a síntese de lipídios com intensa ação ovicida e elevada toxicidade aguda às formas imaturas, e causa nas fêmeas adultas bloqueio da oviposição, resultando na morte até cinco dias devido ao acúmulo de ovos no corpo, como verificado em Tetranychus urticae Koch (Tetranychidae) (WACHENDORFF et al, 2002), além da redução na fecundidade e fertilidade ( VAN POTTELBERGE et al, 2009)…”
Section: Resultados E Discussão Primeiro Experimento (2008)unclassified